2-in-1: catalyst and reaction medium. Issue 1 (9th December 2016) - Haley, Rebecca A.; Mack, James; Guan, Hairong
Abstract : Vials, balls, foils, and pellets used in high-speed ball mills can be catalysts by themselves. Abstract : Mechanochemistry, more specifically high-speed ball milling, has garnered significant attention in several areas of chemistry, particularly for the synthesis of inorganic materials, cocrystals, organic compounds, discrete metal complexes and metal organic frameworks. This methodology is creating exciting research opportunities because, unlike traditional synthesis, a reaction carried out in a high-speed ball mill does not necessarily need a solvent, thus representing an environmentally friendly solution to the issue of solvent waste. This Chemistry Frontiers article delves into a unique area of ball milling that capitalizes on the solventless nature of the synthesis by using reaction vials, balls, foils, and pellets as both reaction medium and the catalyst. Several examples are highlighted, from nanoparticle synthesis and nanocatalysis to using transition metals in their metallic forms as catalysts. This article is aimed to show both the advantages and challenges present in the field, and to spark interest in further development of this research area.